Uji Stabilitas Formula Optimum Masker Gel Peel Off Ekstrak Buah Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) - Nurul Hidayati; Anita Agustina Styawan; Ida Naim Muslimah (STIKES MUHAMMADIYAH KLATEN, 2020)
Mahkota Dewa fruit (Phaleria macrocarpa (Scheff.) Boerl was effective as an anti-acne agent and an optimization formula of Mahkota Dewa fruit extractpeel off gel mask has been carried out but the stability test has not been carried out. This study aims to determine the stability of the optimum formula of Mahkota Dewa fruit extract (Phaleria macrocarpa (Scheff.) Boerl)peel off gel mask. The fruit simplicia of Mahkota Dewa was extracted by soxhletation with 70% ethanol. The thick extract is made into a peel off gel mask with 13.09%PVA and 2.97% HPMC. Stability tests were carried out in 3 cycles using the freeze and thaw method. The evaluations carried out included organoleptic, homogeneity, pH, viscosity, dispersibility, adhesion and drying time. Analyzed data by One Way Anova followed by the LSD (Least Significance Difference) test. The results showed that the peel off gel mask optimization formula stable in storage for 3 cycles which overall meet the requirements of physical properties. The preparation was brown with rose aroma, thick, homogeneous with a pH value of 6 ± 0 and a viscosity value of 400 ± 0. The results of the drying time and spreadability test showed no difference in all cycles. Although the results of the adhesion test showed a significant difference, it was still within the range of good adhesion values.